The Influence of Various Concentrations of MLSS and COD on the Performance of the MBR to Eliminate the Organic Materials and Nitrogen - Beauty Suestining Diyah Dewanti (Agroindustrial Journal, 2017)
The high nitrogen content in the wastewater can also inhibit the performance of microorganisms. It can be overcome by Membrane Bioreactor (MBR) combined with anoxic tanks. Use of membrane can be set aside and the organic materials with high concentrations of nitrogen. From this research are expected to know the influence of various concentrations of Mixed Liquor Suspended Solid (MLSS) and Chemical Oxygen Demand (COD) on the performance of the MBR to eliminate the organic materials and nitrogen in the anoxic condition. This study used activated sludge from wastewater treatment Surabaya Industrial Estate Rungkut (SIER) as an inoculant and 'synthetic' wastewater as the MBR influent. Research variable is the concentration of COD in mg/L and Sludge Retention Time (SRT). The results showed that the overall performance of the MBR is relatively stable and good. % COD removal obtained at the highest permeate COD concentration of 1800 mg/L, reaching 90%. Total number N in permeate is smaller than 0.5 of the amount of total N in influent or % removal > 50%, then the process of denitrification can be said to be successful. For turbidity removal reached 98.47 up to 98.85%. The flux is getting dropped because fouling due to particles that accumulate on the surface layer of the membrane .